Estimasi Produksi Gas Metana Untuk Pemanfaatan Sebagai Sumber Energi Di TPA Talang Gulo, Jambi - Fitrico Sinaga; Dompak MT Napitupulu; Hutwan Syarifuddin (Universitas Batanghari Jambi, 2023)
Landfills (TPA) are a significant source of methane emissions into the atmosphere. In Indonesia, the estimation of methane gas production from a landfill has not been widely carried out. The purpose of this research is to measure production and measure the concentration of methane gas emitted into the atmosphere, assess methane gas emissions as an energy source, and analyze the potential costs and benefits of electrical energy that can be generated from methane gas emissions at the Talang Gulo TPA. The emission data obtained can be used as material for analysis to create a project for developing a gas processing system from a landfill. This estimation approach is carried out in three ways, namely prediction with LandGEM-v302 software, field measurements with methane flux and utilization of methane gas production as an energy source. The LandGEM-v302 simulation results obtained a total landfill gas of 29.96 Gg/year consisting of CH4 of 8.002 Gg/year, CO2 of 21.96 Gg/year and NMOC (non-methane organic compounds) of 0.344 Gg/year. The results of field measurements on the surface of the closed chamber TPA obtained CH4 emissions from TPA Talang Gulo of 4.75 Mg/year. The different characteristics of the landfill surface greatly affect the gas emissions released into the atmosphere. Moisture conditions or water content in the waste also affect the methane emission rate. The electricity potential from methane gas is 15.718 MW so that the cost benefit analysis shows an NPV of Rp. 6,028,622,852.18, B/C Ratio of 0.00196 and IRR of 2.445%.